DDX3X promotes endoplasmic reticulum protein reprogramming via interaction with ERN1 to amplify cerebral ischemia/reperfusion injury - QiaoHui Du; YuQian Liu; JingLong Guo (European Journal of Medical Research)
Abstract Background Reperfusion therapy is a critical intervention to salvage acute cerebral ischemia. However, reperfusion itself induces cerebral ischemia/reperfusion (I/R) injury. Recent evidence suggests that DEAD-box helicase 3, X-linked (DDX3X) and Endoplasmic Reticulum to Nucleus Signaling 1 (ERN1) play pivotal roles in various diseases, particularly those affecting the nervous system. However, the exact roles of DDX3X and ERN1 in cerebral I/R injury remain unclear. Methods We used Sprague–Dawley (SD) rats subjected to middle cerebral artery occlusion (MCAO) surgery and PC12 cells exposed to oxygen–glucose deprivation/reoxygenation (OGD/R) to establish cerebral I/R injury models. Western blotting, immunohistochemistry, and co-immunoprecipitation were employed to assess the expression and interaction of DDX3X and ERN1. CCK-8 assay and flow cytometry were used to evaluate cell viability and apoptosis. Western blotting was performed to measure key endoplasmic reticulum stress (ERS) markers and downstream targets. Pro-inflammatory cytokines were quantified by ELISA. Results DDX3X and ERN1 were significantly upregulated in both OGD/R-treated PC12 cells and MCAO rat brain tissue. Importantly, DDX3X was shown to positively regulate ERN1 expression, leading to increased apoptosis, ERS, oxidative stress, and inflammation in both cellular and animal models. These processes collectively exacerbated cerebral injury, reinforcing the pathological role of DDX3X and ERN1 interaction in the progression of cerebral I/R injury. Conclusion DDX3X enhances cerebral I/R injury by interacting with ERN1, which triggers the reprogramming of endoplasmic reticulum protein responses, amplifying ERS, apoptosis, and inflammation.